MEMBACA MASA DEPAN “ISLAM DAN FIQH NUSANTARA” SEBUAH CATATAN PENGANTAR - Harisuddin, Mohammad Nor (The International Journal of Pegon : Islam Nusantara civilization, 2018)
This paper would like to describe how the inward direction, the Islamic Nusantara core in Islamic civilization in Nusantara. In the exit direction, Islam Nusantara is the future of World civilization. Meanwhile, fiqh is an important part of Islam Nusantara. Therefore, it is very possible, Islam and Fiqh Nusantara to be an important pillar in the world Islamic Civilization. with the uniqueness, and the future of the world, Islam Nusantara deserves to be a pillar of worldcivilization in the days to come. This is because it is not the Middle East again the center of Islamic civilization, but the Center of Islamiccivilization of the world shifted to Indonesia.